Clusterin synergizes with IL‐2 for the expansion and IFN‐γ production of natural killer cells - Sonn, Chung Hee (J Leukoc Biol, 2010)
CLU is a secreted, multifunctional protein implicated in several immunologic and pathologic conditions. As the level of serum CLU was shown to be elevated during inflammatory responses, we questioned if CLU might interact with circulating lymphocytes leading to functional consequences. To assess this possibility directly, mouse splenocytes and purified NK cells were cultured with varying dose of CLU, and its effect on cell proliferation was examined. Our data showed that CLU up‐regulated DNA synthesis and expansion of NK cells significantly in response to a suboptimal, but not maximal, dose of IL‐2, and CLU alone did not exhibit such effects. This CLU‐mediated synergy required the copresence of CLU at the onset of IL‐2 stimulation and needed a continuous presence during the rest of the culture. Importantly, NK cells stimulated with CLU showed increased formation of cell clusters and a CD69 activation receptor, representing a higher cellular activation status compared with those from the control group. Furthermore, these NK cells displayed elevated IFN‐γ production upon RMA/S tumor target exposures, implying that CLU regulates not only NK cell expansion but also effector function of NK cells. Collectively, our data present a previously unrecognized function of CLU as a novel regulator of NK cells via providing costimulation required for cell proliferation and IFN‐γ secretion. Therefore, the role of CLU on NK cells should be taken into consideration for the previously observed, diverse functions of CLU in chronic inflammatory and autoimmune conditions.